Application of Business and Role-Playing Games in the Process of Teaching Medical Students a Foreign Language. - Русалкина, Л. Г. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
Thе article is devoted to the problem of application of business and role-playing games in the process of teaching medical students a foreign language. It has been defined that due to the usage of role and business games students exchange professional knowledge, consolidate skills of communication in English language and find optimal solutions of proper professional problems by means of a foreign language. A business role-playing game allows diversifying the process of teaching in non-linguistic high schools. This method reveals linguistic potential of students, stimulates creative abilities, develops the skills of business communication in a foreign language.